2018
DOI: 10.1016/j.appet.2018.07.025
|View full text |Cite
|
Sign up to set email alerts
|

The duration of intermittent access to preferred sucrose-rich food affects binge-like intake, fat accumulation, and fasting glucose in male rats

Abstract: Many people restrict their palatable food intake. In animal models, time-limiting access to palatable foods increases their intake while decreasing intake of less preferred alternatives; negative emotional withdrawal-like behavior is sometimes reported. In drug addiction models, intermittent extended access drives greater changes in use than brief access. When it comes to palatable food, the impact of briefer vs. longer access durations within intermittent access conditions remains unclear. Here, we provided m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 87 publications
0
10
0
2
Order By: Relevance
“…Latency to eat and intake of sucrose-rich pellets 35 in an unfamiliar double-size cage were measured. Rats received home cage pre-acclimation to the food 24-hr earlier.…”
Section: Methodsmentioning
confidence: 99%
“…Latency to eat and intake of sucrose-rich pellets 35 in an unfamiliar double-size cage were measured. Rats received home cage pre-acclimation to the food 24-hr earlier.…”
Section: Methodsmentioning
confidence: 99%
“…REE Increases the Activity and the Rate of Appetitive USVs in the Cage Several lines of evidence have shown that restricted or unpredictable access to rewarding stimuli (e.g., food or drugs of abuse) increases both incentive motivation attributed to reward-predicting cues and approaching and consummatory responses toward the reward (Anselme et al, 2013;Brenes and Schwarting, 2014;Schultz, 2016;Kreisler et al, 2018). Considering that laboratory rodents prefer larger and complex cages, social contact, and exercise (Olsson and Dahlborn, 2002;Van Loo et al, 2003;Heyse et al, 2015), we assume that EE is rewarding for rodents.…”
Section: Methodsmentioning
confidence: 99%
“…We assumed, therefore, that the benefits derived from EE may be determined by motivational factors related to how much animals attribute incentive salience to such stimulations. The motivational value of an appetitive stimulus can be potentiated through unpredictable presentations (Anselme et al, 2013;Schultz, 2016;Kreisler et al, 2018). Thus, to enhance the rewarding properties of the EE, we developed a protocol in which access to the EE cage was restricted to specific durations ranging from 2 to 48 h unpredictably for 30 days.…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with other animal models of binge-like eating. While limiting access to high-fat diets generally does not affect body weight gain [ 7 , 30 ], conversely, several limited access procedures to sucrose diets have been shown to increase body weight gain [ 4 , 31 , 38 ]. Future studies will be needed to determine the mechanism underlying the different metabolic effects of limited access to the two diets.…”
Section: Discussionmentioning
confidence: 99%